Dust Storm Outbreak in Central Asia After 3.5 kyr BP. Issue 13 (4th July 2019) - Han, Wenxia; Lü, Shuang; Appel, Erwin; Berger, André; Madsen, David; Vandenberghe, Jef; Yu, Lupeng; Han, Yongxiang; Yang, Yibo; Zhang, Tao; Teng, Xiaohua; Fang, Xiaomin
Abstract: The evolution and driving factors underlying dust activity in central Asia remain controversial, particularly in its effects on downwind regions. We present a Holocene dust storm activity record retrieved from the Tarim Basin (TB) and perform linear and nonlinear analyses on dust records from the TB and the Greenland areas. The results indicate a similar response of dust activities to total solar irradiance in both areas, and an outbreak of dust storms in the TB at 3.5 kyr BP. We suggest that decreasing temperature in high northern latitudes, aided by solar activity change, reached a critical threshold near 3.5 kyr BP. The resulting steepening of the meridional temperature gradient would have facilitated strengthening and southward shift of the Northern Hemisphere westerly jet, leading to the outbreak of dust storms through intensification of low level wind intensity and prolonged spring conditions in the Asian interior. Key Points: A possible tipping point of dust activity in central Asia at 3.5 kyr BP was indicated by intensity and regime changes of dust record We identify similar response of dust activities in both central Asia and Greenland areas to solar activity change Insolation and solar activity change drive dust storm outbreak in Asia by increased wind intensity and prolonged spring conditions